Improving Human Resources by Motivating and Developing the Potential of Gen-Z Using Tarot Cards - Tri Rahmadana (Program Studi Pendidikan Biologi, 2025)
This study aims to help motivate and develop self-potential as an effort to improve human resources, especially among Gen-Z (born between 1997 and 2012) by using Tarot cards. Tarot cards are 78 cards that are often used by people to predict luck in terms of finances, love, and life problems in the future as a glimpse of one's life anticipation. This study using Tarot cards aims to provide another view that using Tarot cards will more or less help young generations such as Gen-Z to increase their existing self-potential by providing constructive advice by opening Tarot cards. The research method used is descriptive qualitative with researchers as participant observers. The targets of this study are young people with an age range of 13 to 28 years, born between 1997 and 2012, often referred to as Gen-Z, with the selection of research subject targets using the Purposive Sampling technique . The research results show progress in terms of behavior, which has undergone changes in daily patterns, meaning positive changes in motivating and developing their potential to become better individuals. Tarot cards can be an innovative alternative in efforts to motivate and develop human resources in Generation Z, provided they are supported by appropriate communication strategies and an environment that supports personal growth.